2006
DOI: 10.1152/japplphysiol.00376.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response to hypercapnia and hypoxia after extensive lesion of medullary serotonergic neurons in newborn conscious piglets

Abstract: Acute inhibition of serotonergic (5-HT) neurons in the medullary raphé (MR) using a 5-HT(1A) receptor agonist had an age-dependent impact on the "CO(2) response" of piglets (33). Our present study explored the effect of chronic 5-HT neuron lesions in the MR and extra-raphé on the ventilatory response to hypercapnia and hypoxia in piglets, with possible implications on the role of 5-HT in the sudden infant death syndrome. We established four experimental groups. Group 1 (n = 11) did not undergo any treatment. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 54 publications
4
53
1
1
Order By: Relevance
“…Developmental differences in the role of oropharyngeal sensation during respiration have been noted in previous studies, and the same may be seen for the swallowing reflex as well (Litmanovitz et al 1994;Penatti et al 2006). Additionally, early studies of swallowing in decerebrate cats showed substantial variation in recordings from motor nerves following different oropharyngeal sensory stimulations that resulted in swallows in infants (Sumi 1967).…”
Section: Discussionsupporting
confidence: 62%
“…Developmental differences in the role of oropharyngeal sensation during respiration have been noted in previous studies, and the same may be seen for the swallowing reflex as well (Litmanovitz et al 1994;Penatti et al 2006). Additionally, early studies of swallowing in decerebrate cats showed substantial variation in recordings from motor nerves following different oropharyngeal sensory stimulations that resulted in swallows in infants (Sumi 1967).…”
Section: Discussionsupporting
confidence: 62%
“…The advantage of 5,7-DHT is that it eliminates 5-HT neurons, and thus blocks release of both 5-HT and neuropeptides. The disadvantage is that 5,7-DHT typically reaches only a limited number of 5-HT neurons (Penatti et al, 2006). Therefore, data obtained using either of these approaches can be difficult to interpret.…”
Section: Role Of Central 5-ht Neurons In Respiratory Controlmentioning
confidence: 99%
“…5 A recent study involving chemical ablation of approximately 60% of medullary 5-HT neurons in neonatal piglets reported that males exhibited a blunted response to inspired carbon dioxide during sleep, whereas females responded normally. 40 Of note, this carbon dioxide response is modulated in part by 5-HT 1A receptors in the medullary raphé. 17 This experimental finding raises the possibility that in humans male infants may similarly be less sensitive to carbon dioxide than female infants, and that loss of medullary 5-HT 1A receptors, as observed in the SIDS cases in this study, may attenuate respiratory responses to hypercapnia to a greater extent in male compared with female infants, thus placing them at greater risk for SIDS.…”
Section: Commentmentioning
confidence: 99%